Rethinking Humanity for Counter Terrorism: a Method of Deradicalization in Lingkar Perdamaian Foundation - Noor, Aditia Muhammad (ADDIN, 2021)
Deradicalization is carried out as a form of fostering former terrorists so that they can be rehabilitated both in their actions and in the paradigm they adhere to. Deradicalization should be carried out as far as possible to find out the background of the involvement. The formulation of the problem in this study; how the deradicalization strategy and the implications of the program. This study used the descriptive qualitative method. This study shows that Abraham Maslow’s hierarchy of needs is a strategic step taken by the Lingkar Peace Foundation through ideological development, assistance to convict families and economic recovery. So this step has implications for the love of the country and respect for every difference.